THE EVOLUTION OF CONTRACT LAW IN THE DIGITAL AGE: THE CHALLENGES OF ELECTRONIC CONTRACTS, VIRTUAL BREACHES OF CONTRACT, AND CONSUMER PROTECTION IN THE PLATFORM ECONOMY - Gunawan Widjaja (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2026)
The digital era has triggered a significant evolution in Indonesian contract law, shifting the paradigm of the Civil Code from conventional obligations based on physical documents towards dynamic electronic contracts through the recognition of the Information and Electronic Transactions Act No. 11 of 2008, as amended by Act No. 1 of 2024, where this transformation faces challenges regarding the authentication of digital signatures, the proof of transaction data integrity, and the role of e-commerce platforms as subjects of multilateral contractual liability within a platform economy valued at Rp 500 trillion by 2025. This normative-legal study analyses the dynamics of virtual breach of contract in the form of non-delivery of goods, algorithmic system errors, and the manipulation of fake reviews—which are subject to Articles 1234–1246 of the Civil Code but require digital forensics to establish causality—as well as the evaluation of the effectiveness of consumer protection under the Consumer Protection Act No. 8 of 1999 and the Personal Data Protection Act No. 27 of 2022 against information asymmetry and misleading practices on marketplaces such as Shopee and Tokopedia. The analysis reveals a regulatory gap between the static norms of the Civil Code and the dynamics of blockchain smart contracts and the gig economy, where adaptive solutions include integrated Online Dispute Resolution (ODR), automatic escrow payments, and joint and several liability of platforms and sellers to mitigate virtual breach of contract, whilst reform recommendations include a dedicated digital contracts law, strengthening the BPSK for e-commerce mediation, and consumer legal literacy to realise a fair transaction ecosystem in line with the ASEAN Digital Economy 2030 vision.